Understanding university students’ recycling behaviours: an analysis using the theory of planned behaviour / Nor Adilla Yusoff ... [et al.] - Yusoff, Nor Adilla; Azmi, Alia; Abd Aziz, Nor Azimah; Ghazali Masuri, Mohammad; Danis, Ajau; Isa, Siti Nor Ismalina; Ilias, Kartini; Loganathan, Mathumalar; Md Isa, Khairil Anuar (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
This cross-sectional study aimed to elucidate the determinants of recycling behaviour among university students employing the Theory of Planned Behaviour (TPB) as the analytical framework. Of the 176 participants, 76% (n=134) reported engaging in recycling activities on campus. A significant association was observed between on-campus residency and recycling behaviour (p=0.01). No significant association were found between recycling habits and either the students' degree courses (p=0.12) or area of origin (p=0.24). Attitudes towards recycling emerged as a crucial predictor, with notable findings in the TPB constructs (p<0.05). Similarly, subjective norms, reflecting social pressures, also significantly influenced recycling intentions (p<0.05). Moreover, perceived behavioral control was also identified as a significant determinant of recycling behaviour among students (p<0.05). The study underscores the integral roles of attitudes, subjective norms, and perceived behavioral control in shaping recycling behaviour among university students. The significant link between residency status and recycling suggests that targeted educational and awareness programs could enhance recycling practices. These findings provide a foundation for universities to develop strategic interventions that foster sustainable behaviours, thereby contributing to environmental conservation efforts. In conclusion, the application of the TPB highlights the multifaceted nature of recycling behaviours, offering critical insights for promoting sustainability within academic institutions.